Inherent flexibility and protein function: The open/closed conformational transition in the N-terminal domain of calmodulin - Tripathi, Swarnendu; Portman, John J (The Journal of chemical physics, 2008)
The key to understand a protein's function often lies in its conformational dynamics. We develop a coarse-grained variational model to investigate the interplay between structural transitions, conformational flexibility, and function of the N-terminal calmodulin domain (nCaM). In this model, two energy basins corresponding to the "closed" apo conformation and "open" holo conformation of nCaM are coupled by a uniform interpolation parameter. The resulting detailed transition route from our model is largely consistent with the recently proposed EFbeta-scaffold mechanism in EF-hand family proteins. We find that the N-terminal parts of the calcium binding loops shows higher flexibility than the C-terminal parts which form this EFbeta-scaffold structure. The structural transition of binding loops I and II are compared in detail. Our model predicts that binding loop II, with higher flexibility and earlier structural change than binding loop I, dominates the open/closed conformational transition in nCaM.